Reconstruction of the historical temperature trend from measurements in a medium-length borehole on the Lomonosovfonna plateau, Svalbard - Van de Wal, Roderik S.W.; Mulvaney, Robert; Isaksson, Elisabeth; Moore, John C.; Pinglot, Jean Francis; Pohjola, Veijo A.; Thomassen, Martijn P.A. (Annals of Glaciology, 2017)
A medium-length ice core was drilled at the ice divide on the Lomonosovfonna plateau (1230 m a.s.l.), Svalbard, in May 1997. As part of this project, temperature measurements were performed in the 120 m deep borchole. At this site the ice thickness based on radar measurements is 126.5 m and the mean annual accumulation rate is 380 kg m -3 . The measurements over the 15-120 m depth interval show a nearly isothermal profile with a mean value of -2.8°C and a standard deviation of 0.2°C. The measurements reveal a temperature minimum at approximately 70 m depth and a temperature gradient of 0.011 ± 0.004°C m -1 near the bottom. The temperature minimum and relatively low temperature gradient cannot be explained in terms of a steady-state climate. Numerical calculations with a simple one-dimensional diffusion-advection model show that the temperature increased at a maximum rate of 0.02-0.025 K a -1 over the last 100 years, the total temperature increase amounting to 2.0-3.0 K. Forcing the model with the observed record at Svalbard airport revealed that in the 19th century the surface temperature was at most 2.5 K lower, and that the instrumental observations started during a period with temperatures comparable to the end of the 19th century. The data are of particular interest for historical simulations since often no other temperature data are available in polar areas.